Analisis Kemampuan Pemecahan Masalah Matematis Pada Materi Bangun Datar Siswa Kelas V SD Tambirejo Demak - Setiyawati, Heny Septyan; Putri, Rizqi Dian Yulia; Riswari, Lovika Ardana (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2023)
This study aims to determine and analyze the mathematical problem solving abilities of SD Tambirejo student. This study used qualitative research methods.The subject of the research taken were 37 students. Data collection was carried out bay providing problem solving test questions in the form of 4 description questions with flat shape material.The analysis was carried out with the attainment of indicators of mathematical problem ability in Harisuddin’s writing, namely there were 4 indicators of mathematical problem solving with each questions fulfilling the indicators.The result of the reseach from the data that had been taken sowed that there were 25 student who answered incorrectly on questions number 4 and on questions number 1 to 3 student were still able to descrip their answers in the correct way.